Use of ozone therapy as an auxiliary mechanism in the treatment of wound in horses: Literature review (Research, Society and Development, 2024)
Equine medicine has been evolving every day and with this, new therapeutic methods have also emerged along with its evolution. Ozone therapy has been one of these evolving treatments, being increasingly studied and applied, and specifically, with regard to the treatment of wounds, which is still a challenge in the area, it presents satisfactory results in its use. With the main objective of increasing tissue oxygenation and consequently, improving the healing of various types of wounds, it has also been effective as an anti-inflammatory, antibacterial and antifungal, in addition to helping to control pain, edema and hyperpermeability in wounds. Ozone also has several application routes, which facilitates the management of the treatment of tissue injuries and wounds of the most diverse degrees and locations. Even so, adequate knowledge about the use of the technique and its application is extremely important. The aim of this study was to conduct a literature review addressing the use of ozone therapy for the treatment of various wounds in horses, providing relevant information on the advantages of its application.